The accuracy of shooting petanque iron balls: Effectiveness of resistance band training - Rasyono; Yanto, Anggel Hardi (Journal Sport Area, 2024)
Background Problems: There is an integration of strategy, calmness, and accuracy in petanque. Various training forms focus on several parts of the arm muscles to increase the stability of the arm muscles and the ability to throw the ball on target, however, no one has developed a training method that can enhance both accuracy and muscular strength. Research Objectives: This research aims to determine the effect of resistance band exercises on shooting accuracy in petanque athletes. Methods: This research employed a quasi-experimental method with a pretest-posttest approach and a control group design. The research subjects were divided into two groups (experimental and control) and given different treatments. The total number of research subjects consisted of 40 athletes with an average age of 21.43  ± 2.48, a weight 56.07  ± 2.33, a height 170.41  ± 5.12, and a BMI 19.86  ± 2.56. Data analysis was tested using a one-way ANOVA to compare the two groups. Findings and Results: The research results indicated that resistance band exercises for 16 weeks had a positive and statistically significant impact on increasing shooting accuracy in the experimental group compared to the control group in petanque athletes. Thus, this research has provided evidence and recommendations for athletes and coaches that specific recommendations to improve throwing accuracy in petanque must be added with the contribution of strength training with resistance bands. Conclusion: The combination of resistance bands with other forms of accuracy training is also recommended for further research so that options for implementing strength training related to throwing accuracy become more varied to help improve petanque performance. This study can be used as a starting point for training variations that are documented in the literature, which can help coaches and athletes develop skills-related fitness components for the purpose of improving shooting accuracy capabilities in petanque.